America's search for security the triumph of idealism and the return of realism - Kay, Sean 1967- (Rowman & Littlefield, 2014)
This book details the ways in which America's ascendancy to global superpower status was the result of its dueling foreign policy philosophies and forces: an historically expansive idealism balanced with an equally constant realist restraint.